Tawhid and Shariah Economics: Positioning Tauhid as Philosophical Foundation of Shariah Economics - Nurul Hilmiyah; Bayu Taufiq Possumah; Muhammad Hakimi Mohd Shafiai (AL-FALAH : Journal of Islamic Economics, 2019)
Purposes: In the social sciences, economics is one of the most influential and prestigious disciplines. Mainstream economics typically view economic agent as amoral, entirely self-interested, unrealistic and has damaging effects. In the last few decades, while remaining a powerful discipline, economics has narrowed in scope. Consequently, to reinvigorate economics, especially in times of crisis or major institutional change, mainstream economics has almost lost a key reserve of alternative thinking. This study intends to investigate the contemporary mainstream economic system, does Islamic Economics taking advantage of the shortfall of the system outlined above based on Tawhidical approach?Design/Methodology/Approach: This paper using the descriptive qualitative method Findings: Modern economics is normative bias; does not explain actual economies but describes a "utopia" in which Pareto optimality applies. The excessive unrealistic assumption is the impact of the inconsistency of modern economic theory. The important aspects of human behavior ignored by this assumption as the theory of economic man. In addition, the general equilibrium theory of neoclassical is not compatible with an economy that develops over time. It relies too much on complex mathematical models without sufficient attention to whether this really illustrates the real economy and ignores the complexity of nature and human creativity. At the contrary, Islam cause to be present the Tawhidic based economics approaches can be focused towards seeing wholes of economics, rather than parts; seeing economics activities as worship, rather than competition; cultivating the solidarity (charity), rather than individualism and creating the justice, rather than injustice. Thus this paper designed to provide the concept of Islamic economic system with Tawhid as the basis, to fit the philosophy of economic science and reality of human life. The paper shows the position of Tawhid in the system and theory of economy.  It becomes a must to do to create prosperity and benefit for all mankind, with the aim to realign and comparing to the mainstream economic system and their theory.Originality/Value: This paper proposes the position of Tawhidic based economics approach in setting the economic system. The position of this foundation offers basic guidelines for the justice and fairly system, which is benefited to all human beings regardless of religions, races, and castes, and furthermore to the sustainable economic development and welfare for the ummah.